Preparing for the Research Ceremony: Indigenist Researcher Training. (March 2023) - Hughes, Margaret; Wilson, Shawn; Barlo, Stuart
Preparing ourselves for the ceremony of research is akin to preparing ourselves to be in good relationship with Knowledge, and with whoever else participates in the research, including other human beings, more than human beings, and Country. In this article, I talk about the practice of cultivating the values and skills that make for good relationships, both as a researcher in training and through the mentoring relationships with my PhD supervisors. It is my hope that sharing my experience as a PhD student traversing this training and mentoring journey may support others preparing for research within a relational methodology. Throughout the conversation, I come back to the importance of cultivating and practicing the principles of respect, receptivity, generosity, humility, compassion, and care, and building the skills of attention, deep listening, and service.